METODE TAFSIR DAN MACAM-MACAMNYA - Nanda Fitriyah; Ani Safitri; Aprillia Ajeng; Umar Al-Faruq (Pondok Pesantren Baitul Qur`an Sambas, 2024)
The Al-Qur'an is a collection of revelations from Allah SWT which were revealed to the Prophet Muhammad SAW in Arabic as a guide for mankind at that time and continues to be valid until the end of time. It is universal, not limited by the dimensions of time and place. In accordance with the function and position of the Koran, it is very large. For this reason, determining the procedures for interpreting the Qur'an needs to be formulated so as to avoid confusion in interpretation. There are several methods for interpreting the Qur'an, including various approaches to interpretation methods that have been developed by scholars to achieve a broader understanding. Interpreting the Qur'an includes four methods, namely the tahlili method, ijmali method, muqaran method, and mawdhu'I method. The method of interpreting the Koran is not something that can be simply ignored. Understanding of the methodology must be pursued continuously towards its refinement.